A computational literature review of the field of System Dynamics from 1974 to 2017. Issue 2 (3rd April 2018) - Kunc, Martin; Mortenson, Michael J.; Vidgen, Richard
Abstract: System Dynamics celebrated its 60th anniversary in 2017. While there have been numerous special issues in diverse journals that bring together work by System Dynamics scholars who share similar research interests, there have been no systematic reviews of scholarly activity across the broad field. This paper presents a computational literature review of the field from 1974 to 2017. A CLR automates the analysis of research articles with analysis of content (topic modelling of abstracts) to identify emergent themes in the literature. We performed a broad review of the field by initially searching using the term "System Dynamics" with more than 8000 articles. However, the results obtained were not satisfactory so we decided to restrict our sample to less than 800 articles from recognised journals and proceedings. After evaluation of the results obtained from topic modelling, we decided to use 51 topics covering most of the articles in our sample. A list of 51 topics provides enough granularity to identify relevant patterns of activity within the community of System Dynamics scholars. For each of these 51 topics, we present a commentary on the key insights obtained.